2023
DOI: 10.3389/fonc.2022.1022305
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound and shear wave elastography in the diagnosis of ACR TI-RADS 4 and 5 category thyroid nodules coexisting with Hashimoto’s thyroiditis

Abstract: ObjectiveThis study aims to evaluate the value of contrast-enhanced ultrasound (CEUS), shear wave elastography (SWE), and their combined use in the differentiation of American College of Radiology (ACR) thyroid imaging reporting and data system (TI-RADS) 4 and 5 category thyroid nodules coexisting with Hashimoto’s thyroiditis (HT).Materials and methodsA total of 133 pathologically confirmed ACR TI-RADS 4 and 5 category nodules coexisting with HT in 113 patients were included; CEUS and SWE were performed for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Therefore, it is of more clinical signi cance to improve the diagnostic e cacy for ACR TI-RADS4 nodules. CEUS and SWE can enhance the diagnostic e cacy for thyroid nodules, and the combination of the two has even better diagnostic e cacy [15]. At present, no research on the construction of diagnostic models using CEUS and SWE quantitative parameters has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is of more clinical signi cance to improve the diagnostic e cacy for ACR TI-RADS4 nodules. CEUS and SWE can enhance the diagnostic e cacy for thyroid nodules, and the combination of the two has even better diagnostic e cacy [15]. At present, no research on the construction of diagnostic models using CEUS and SWE quantitative parameters has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [28] found that the diagnostic sensitivity and speci city of contrast-enhanced ultrasound plus shear-wave elastography were 93.38% and 92.89%, respectively. Wang et al [15] found that the AUC, sensitivity, speci city, and accuracy of contrast-enhanced ultrasound plus shear-wave elastography are 0.800, 94%, 66%, and 83.5%, respectively. Huang [29] found that the AUC, sensitivity, and speci city of contrast-enhanced ultrasound plus shear-wave elastography were 0.937, 91.67%, and 95.65%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of more clinical significance to improve the diagnostic efficacy for ACR TI-RADS 4 nodules. CEUS and SWE can enhance the diagnostic efficacy for thyroid nodules, and the combination of the two has even better diagnostic efficacy [ 19 ]. In this study, we intend to try to apply the quantitative analysis parameters of ultrasonography and the quantitative analysis parameters of shear wave elastography to construct a predictive model for category 4 nodules, in order to ware to improve the malignancy detection rate of suspicious nodules among the category 4 nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 32 ] found that the diagnostic sensitivity and specificity of contrast-enhanced ultrasound plus SWE were 93.38 and 92.89%, respectively. Wang et al [ 19 ] found that the AUC, sensitivity, specificity, and accuracy of contrast-enhanced ultrasound plus SWE were 0.800, 94, 66, and 83.5%, respectively. Huang [ 33 ] found that the AUC, sensitivity, and specificity of contrast-enhanced ultrasound plus SWE were 0.937, 91.67, and 95.65%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether HT increases thyroid cancer risk in individuals with TNs is controversial and remains to be defined[ 111 , 112 ]. Therefore, to avoid overtreatment with surgery in HT patients with TNs without any other evidence of malignancy as well as to predict the malignancy risk of these TNs accurately, various ultrasound-based diagnostic classification systems, which have been developed for differentiating benign and malignant TNs, may represent a critical role in detecting malignant TNs in HT individuals[ 113 - 116 ]. Moreover, in some cases with difficult diagnoses, ultrasound-guided FNAB can be used as an effective, less-invasive approach to confirm the nature of the lesion and propose the most beneficial/optimal treatment[ 117 , 118 ].…”
Section: Ultrasonography Application In Aitdmentioning
confidence: 99%